Improving Fourth Grade Students’ Procedural Text Writing Skills Through Problem Based Learning at SD Negeri 4 Buntok - Puji Astuti; Esti Swatika Sari (Universitas Islam Negeri Palopo, 2026)
This classroom action research examined the use of Problem-Based Learning (PBL) to improve procedural text writing among 26 fourth-grade students at SD Negeri 4 Buntok. The study followed two cycles of planning, action, observation, and reflection. Data were collected through observation, writing tests, and documentation and analyzed descriptively. Success was defined as active participation by at least 80% of the class and a score of 70 or higher for at least 75% of the students. The findings indicate improvement in classroom participation and writing quality. Students became more active in problem analysis, group discussion, drafting, presentation, and revision. Their later texts showed clearer goals, materials, and ordered steps, together with more appropriate imperative sentences, action verbs, temporal conjunctions, spelling, and punctuation. The source manuscript also reports increased mean scores and classical mastery across the cycles, but the final values require author verification because the original abstract and conclusion contain conflicting figures. Overall, contextual problem solving, collaboration, and teacher feedback supported more coherent and functional procedural texts.